2003
DOI: 10.2320/matertrans.44.401
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Boron Carbide-Silicon Carbide Composite at 1073 to 1773 K

Abstract: The oxidation behavior of B 4 C-(25-60 mol%)SiC composites prepared by arc-melting was investigated in the temperature range of 1073 to 1773 K using a thermogravimetric technique. Liquid borosilicate, solid SiO 2 and carbon were identified as oxidation products by X-ray diffraction and Raman spectroscopy. Mass gain was observed during oxidation at 1073 K, while mass loss due to the vaporization of boron oxide in liquid borosilicate was observed at temperatures of 1273 K and higher. In situ Raman spectra of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
8
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
9
8
3
Order By: Relevance
“…In contrast with previous Raman results of thermally grown borosilicate glasses formed from oxidation at 600°C and 800°C, peaks assigned to the B 2 O 3 boroxol ring at ~800, 808 cm −1 (Figure , dotted line) in their studies are absent in this study. According to Narushima et al, this B 2 O 3 peak is a function of the boria concentration in the borosilicate glass. The thermally grown borosilicate glasses in the study by Quemard et al were either pure boria or boria enriched, based on their vibrational spectroscopic results, and further supported by quantitative surface analyses that determined molar ratios of B 2 O 3 : SiO 2 ranging from ~1.3:1 to 4.8:1.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast with previous Raman results of thermally grown borosilicate glasses formed from oxidation at 600°C and 800°C, peaks assigned to the B 2 O 3 boroxol ring at ~800, 808 cm −1 (Figure , dotted line) in their studies are absent in this study. According to Narushima et al, this B 2 O 3 peak is a function of the boria concentration in the borosilicate glass. The thermally grown borosilicate glasses in the study by Quemard et al were either pure boria or boria enriched, based on their vibrational spectroscopic results, and further supported by quantitative surface analyses that determined molar ratios of B 2 O 3 : SiO 2 ranging from ~1.3:1 to 4.8:1.…”
Section: Resultscontrasting
confidence: 99%
“…Although formation of the low viscosity glass sealed the matrix cracks, considerable SiC fiber recession adjacent to regions of a thick borosilicate glass was also observed . Other studies found the oxidation rates of Si‐based materials to accelerate in the presence of boron (B) . Parabolic rate constants (k p ) from a few of these studies conducted at 800°C are extrapolated here to 1 atm of dry oxygen (O 2 ) using derived SI units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the 1200˚C kp for CVD-SiC reported by Ogbuji and Opila 17 , it would take 9.9 h to grow an equivalent SiO2 oxide thickness. This order of magnitude increase in SiC oxidation kinetics is in line with others 23,39,41 who also observed orders of magnitude increases in the oxidation kinetics of Si-based materials due to the presence of B2O3.…”
Section: Oxidation Resultssupporting
confidence: 91%
“…Si, Mg, Nb, Ti, Cu, and some rare earth elements cannot only enhance the bonding between SiC and Al but also increase the matrix strength (Gu et al, 1999;Starink et al, 1999;Lee et al, 2001;Lima et al, 1999). The oxidation layer of SiO 2 on the surface of SiC particles was reported to facilitate the wetting between SiC and Al at the interface (Narushima et al, 2003;Tang et al, 2001). * Corresponding author.…”
Section: Introductionmentioning
confidence: 96%